Easy Ways to Overcome Floods With an Economical Weir Form - Rendy Kurnia Dewanta; Fitry Rahmawaty; Evita Fitrianis Hidiyati (LEADER: Civil Engineering and Architecture Journal, 2023)
The increased risk of flooding due to climate change is cause concern because it causes economic losses in various regions of the world. Flood control planning is needed so that floods that occur do not have a negative impact on life, especially in the economy. One way of flood control is to use weirs. Weirs are able to withstand the flow of water upstream of rivers or large waterways, limiting the flow of water entering downstream. By regulating the flow of water, the weir can reduce the possibility of flooding downstream. Part of the weir building is the threshold which has several commonly used shapes and each shape has its own advantages The purpose of this practicum is to determine the discharge of water flowing with thresholds, namely triangular thresholds and sharp thresholds with variations in door openings. The method used is to conduct testing in the Civil Engineering Laboratory using a replica of a river (open channel) along 10 meters. When testing the flow velocity is also calculated. The result of the test is obtained discharge data that flows with thresholds. The smallest flow discharge is obtained at the triangular threshold with a downstream opening of 1 cm. The effect of discharge on flood management is that if a river flow has a large discharge capacity, you can use the results of this calculation as a reference to overcome the problem.